Time to Eat Your Vegetables: The Role of Circadian Clocks in Insect Herbivory. - Smith, L.; Tyler, C.J.; Mahajan, S.; Okamoto, H.; Wijnen, H. (Insects, 2026)
Insects exhibit a range of ecological relationships with plants, including pollination, seed dispersal, parasitism, predation, and herbivory. Interactions between insects and plants are shaped by internal daily timekeeping systems in both sets of organisms termed circadian clocks. This review describes the impact of the circadian clocks of insects and plants on herbivory, which is highly relevant not only to natural ecosystems, but also to agriculture and forest management. Following an introduction to the circadian clocks of plants and insects, we discuss the circadian organization of relevant aspects of plant metabolism and defense. Next, we describe how insect clocks govern herbivory-associated physiology and behavior before exploring how rhythmic processes in plants and insects interact to temporally control herbivory. Finally, we describe how insights from the clock control of herbivory may inform pest management strategies and what future research in this area may contribute.